Arquivo, história e memória : o processo de constituição e patrimonialização de um acervo privado (a Coleção Varela – AHRS, 1858/1936) - Silva, Camila (Universidade do Vale do Rio dos Sinos, 2019)
This work analyzes the path of constitution and patrimonialization of the Varela Collection, one of the main collections on the Farroupilha Revolution. In the late 1850s, Domingos José de Almeida iniciated the archive collection on the civil war of 1835. The former minister of Farroupilha intended to publish a documented history of the Rio-Grandense Republic in the journal “O Brado do Sul”. Later this files was offered to the historian Alfredo Varela, an important reference on the revolt of farrapos, civil war that occurred between 1835 and 1845. The “História da Grande Revolução”, his best known work, was written with the files preserved in this archive. In 1936, this collection was donated to the Government of the State of Rio Grande do Sul. The research aims to denaturalize the process of accumulation of the generating sources of the set, through the understanding of the agents (individual and institutional) that intervened in the selection and preservation of their documents. In this sense, we investigate three phases that we consider to be the main ones in its path: 1) the collection of documents and the establishment of sources for the writing project of the Farroupilha Revolution’s history, by Domingos José de Almeida; 2) the management and uses of the collection in the historiographical operation of Alfredo Varela; 3) the transition from custody of the Varela Collection to the public domain.
Keywords: Arquivo; Coleção Varela; Patrimônio; Revolução Farroupilha; Archive; Varela Collection; Historical Heritage; Farroupilha Revolution; ACCNPQ::Ciências Humanas::História